Window shopping : a novel - Bailey, Tessa (Avon, an imprint of HarperCollins Publishers, 2024)
"Two weeks before Christmas and all through Manhattan, shop windows are decorated in red and green satin. I'm standing alone in front of the famous Vivant department store, when a charming man named Aiden asks my opinion of the décor"--